Beyond Binary: A Holistic Exploration of Fuzzy Logic Systems in Control Theory-An Extensive Review and Future Directions - Ancy A.S.; Farsana Muhammed (International Journal of Electrical Power and Machine Systems, 2024)
Now a days non renewable energy or conventional energy sources are reduced due to the increased usage of energy for several purposes, for that renewable energy source are introduced for the same. This help islanded areas electrification, several methods are used for the storage and distribution of energy. one of the technique is fuzzy logic control, in this paper discuss about the usage of energy and fuzzy logic system usage and its applications.in this paper discuss about the reviews of these methods and its limitations results etc. Fuzzy logic is used in a number of controllers because it does not require an accurate model of the system to be controlled. Fuzzy logic works by executing rules that correlate the controller inputs with the desired outputs. In this paper focus about the controller application in PV and renewable sources.
Keywords: DG units; DOB; FUZZY LOGIC; battery storage; multi agent